KUALITAS KEHIDUPAN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR DI DISNAKER DEMAK - Febry Indra Kristikusuma; Sutarto Wijono (Journal of Innovation Research and Knowledge, 2026)
Currently, organizations recognize the increasing importance of human resources as the primary asset for sustaining the organization. Organizational Citizenship Behavior, which refers to voluntary employee behaviors that exceed their duties, such as helping colleagues, has become the focus of research because it can enhance organizational productivity. On the other hand, Quality of Work Life encompasses aspects such as job satisfaction, balance between personal and professional life, safe working conditions, and opportunities for self-development, all of which contribute to employee well-being. This study aims to examine the relationship between quality of work life and Organizational Citizenship Behavior among employees of Disnaker Demak. The method used is quantitative research with 50 participants, utilizing the Organizational Citizenship Behavior Scale and Quality of Work Life Scale (QWOL), then analyzed using SPSS version 25, resulting in a significant relationship between the variables Organizational Citizenship Behavior and Quality of Work Life with an r value of 0.696 and p < 0.05. The research results indicate a significant positive relationship between the variables Organizational Citizenship Behavior and Quality of Work Life; the higher the level of OCB among employees, the higher their QWL, and conversely, the lower the level of OCB, the lower the QWL